2017
DOI: 10.1111/eci.12803
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin and galanin responses to orthostasis in older persons

Abstract: Adrenomedullin and galanin concentrations were similar between genders and did not change following adoption of the standing posture. To further clarify the roles, these hormones play in orthostatic intolerance, adrenomedullin and galanin concentrations should be assessed in participants who show presyncopal symptoms during an orthostatic challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…A systematic review by Heinrich et al ( 2010 ) indicates that 0.85–1.5% of all health care costs are dedicated solely to the consequences of falls. Therefore, understanding the mechanisms that contribute to falls as well as how risk of falls and falls-related injuries can be reduced is an important aspect in geriatric healthcare delivery (Blain et al, 2016 ; Bousquet et al, 2017 ; Broadbent et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review by Heinrich et al ( 2010 ) indicates that 0.85–1.5% of all health care costs are dedicated solely to the consequences of falls. Therefore, understanding the mechanisms that contribute to falls as well as how risk of falls and falls-related injuries can be reduced is an important aspect in geriatric healthcare delivery (Blain et al, 2016 ; Bousquet et al, 2017 ; Broadbent et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…X 53 Adrenomedullin and galanin concentrations were similar between genders and did not change following adoption of the standing posture. To further clarify the roles, these hormones play in orthostatic intolerance, adrenomedullin and galanin concentrations should be assessed in participants who show presyncopal symptoms during an orthostatic challenge.…”
Section: Bmentioning
confidence: 93%
“…The evidence that has accumulated in the meanwhile weakens this statement. We recently investigated hormonal responses (adrenomedullin and galanin) during a sit-to-stand protocol in older males and females [96]. We observed that adrenomedullin and galanin levels were similar between gender and did not change during standing.…”
Section: Involvement Of Leucocyte/endothelial Cell Interactions In Anmentioning
confidence: 94%